온도 변화 방법과 압력을 이용한 계란 내부로 다시마 추출물의 침투 효율 - 박여진; 김동호(Dong-Ho Kim); 장금일(Keum-Il Jang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
In this study, the permeation efficiency (PE) of sea tangle (Laminaria japonica) extract (STE) into egg using the temperature change method (TCM) and pressure was investigated. STE was prepared in a volume of water equal to 10 times the weight of the sea tangle at $100^{°}C$ over a 3 hr period. The PE of iodine as a representative component of the STE as well as the total polyphenol content at ambient pressure were determined as follows: 1) after soaking in the STE at 30, 40, and $50^{°}C$ for 3 hr, and 2) after soaking in the STE at $4^{°}C$ immediately after soaking in distilled water at $50^{°}C$ for 1, 2, and 3 hr (TCM), respectively. The PE of iodine as well as the total polyphenol content improved as the temperature of the STE increased (P<0.05). The permeation of iodine was more rapid, and the total polyphenol content increased with the TCM (121 ${μ}g/100$ mg and 1.74 mg/mL for 3 hr, respectively) compared to without the TCM (72 ${μ}g/100$ mg and 1.48 mg/mL for 3 hr, respectively), and the highest PE was observed with the TCM after soaking at $50^{°}C$ for 3 hr. At a pressure of 5.0 MPa, the PE was more rapid with the TCM (139 ${μ}g/100$ mg and 1.74 mg/mL for 90 min, respectively) than without the TCM (105 ${μ}g/100$ mg and 1.56 mg/mL for 90 min, respectively). Consequentially, these results suggest that the preparation of seasonings and functional eggs using various components and bioactive substances is possible by the TCM. 본 연구에서는 온도 변화 방법과 압력을 이용하여 계란 내부로 다시마 추출물의 침투 효율을 분석하였다. 다시마 추출물은 $100^{°}C$에서 3시간 동안 다시마 무게의 10배(w/w)의 증류수를 가하여 열수 추출하였다. 대기압에서 다시마 추출물의 지표 성분으로 요오드와 총 폴리페놀의 침투 효율은 30, 40, $50^{°}C$에서 3시간 동안 침지시킨 다음 침투된 요오드와 총 폴리페놀 함량을 측정함으로써 분석하는 경우와 $50^{°}C$에서 3시간 동안 예열한 다음 $4^{°}C$로 온도 변화를 유동하여 침지시켜 침투된 요오드와 총 폴리페놀 함량을 측정함으로써 분석하였다. 요오드와 총 폴리페놀 함량의 침투 효율은 침투 온도가 증가할수록 향상되었다. 그리고 요오드와 총 폴리페놀의 침투는 온도 변화를 하지 않은 경우 각각 3시간 동안 72 ${μ}g/100$ mg과 1.48 mg/mL가 침투된 반면, 온도변화를 유도한 경우 각각 3시간 동안 121 ${μ}g/100$ mg과 1.74 mg/mL가 침투되어 침투 효율이 증가되었으며, $50^{°}C$에서 3시간 예열한 다음 $4^{°}C$로 온도 변화하여 3시간 침투시킨 계란에서 가장 높은 침투 효율을 나타내었다. 그리고 5기압의 압력 조건에서 온도 변화를 유도하지 않고 $50^{°}C$에서 90분간 침투시킨 경우 침투된 요오드와 총 폴리페놀 함량이 각각 105 ${μ}g/100$ mg과 1.56 mg/mL로 나타난 반면, 온도 변화를 유도한 경우 각각 139 ${μ}g/100$ mg과 1.74 mg/mL의 함량을 나타내어 압력에 의해 온도 변화 방법의 침투 효율은 향상되었다. 따라서 본 연구에서는 온도 변화 방법과 압력조건을 통하여 계란 내부로 다시마 추출물의 향상된 침투효율을 확인하였으며, 이는 다시마 추출물 이외의 다양한 조미성분과 기능성 식품 소재의 침투 가능성을 제시함으로써 효율적인 직접 소비가 가능한 계란 가공 공정의 확립이 가능할 것으로 기대된다.